2004
DOI: 10.1111/j.1744-7429.2004.tb00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest Fragmentation on Pollinator Activity and Consequences for Plant Reproductive Success and Mating Patterns in Bat‐pollinated Bombacaceous Trees1

Abstract: Forest fragmentation and the resulting spatial isolation of tree species can modify the activity of pollinators and may have important implications for the reproductive success and mating systems of the plants they pollinate. The objectives of this study were to (1) evaluate the effect of forest fragmentation on pollinator activity in bat‐pollinated bombacaceous trees and (2) determine the effects of forest fragmentation on reproductive success and mating systems of bombacaceous trees. We studied these paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 45 publications
2
77
1
13
Order By: Relevance
“…There is, however, significant variation in the Malvaceae, with a number of species exhibiting mixed mating systems . Notably the genus Ceiba has shown outcrossing and mixed mating varying both within and among species (Quesada et al, 2004). Controlled pollinations in this study showed a varied ability to self among P. quinata trees, with 50% of trees failing to self, whereas 12.5% showed high seed set under selfing.…”
Section: Variable Selfingmentioning
confidence: 85%
“…There is, however, significant variation in the Malvaceae, with a number of species exhibiting mixed mating systems . Notably the genus Ceiba has shown outcrossing and mixed mating varying both within and among species (Quesada et al, 2004). Controlled pollinations in this study showed a varied ability to self among P. quinata trees, with 50% of trees failing to self, whereas 12.5% showed high seed set under selfing.…”
Section: Variable Selfingmentioning
confidence: 85%
“…Indeed, as far as we are aware, there are currently only five published studies of open-pollinated Neotropical trees that have associated changes in mating patterns of individual trees caused by habitat disturbance with proxies of fitness (Rocha and Aguilar, 2001;Cascante et al, 2002;Fuchs et al, 2003;Quesada et al, 2004;Breed et al, 2012), and a single study conducted from Japan (Hirayama et al, 2007). As expected, selfing (4 of 6 studies), biparental inbreeding (2 of 3 studies) and correlated paternity (3 of 4 studies) tended to be negatively associated with fitness.…”
Section: Introductionmentioning
confidence: 92%
“…Isolated populations may receive fewer flower visitors because of the decline in the richness and abundance of pollinators, modifications in species composition and limitation in movement among patches (Cascante et al, 2002;Goverde et al, 2002;Quesada et al, 2004). However, an increased number of studies has been showing that long-distance pollen flow is common in Neotropical trees (Hamrick and Murawski, 1990;Nason et al, 1998; Latouche-Hallé et al, 2004; Dunphy and Hamrick, 2007) and also that gene flow may occur between forest fragments and isolated remnant trees (White et al, 2002, Dick et al, 2003.…”
Section: Introductionmentioning
confidence: 99%